Revitalizing Islamic Ethics Toward Parents and Teachers in the Grade 10 Aqidah Akhlaq Curriculum - Fangsuri, Fatich Ya'i; Muniron (Published by Center for Research and Community Service (LP2M) in cooperation with the Postgraduate Program of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2026)
This study examines the construction of Islamic ethics concerning respect for parents and teachers in the chapter